Tingkat Kerusakan Hama Penggerek Batang Ubi Jalar (Omphisa Anastomosalis) pada Perlakuan Berbagai Jenis Mulsa - Ahmad Riza Prasetiyo; Bambang Supeno; Wahyu Astiko (Pusat riset dan Inovasi Nasional, 2026)
Sweet potato (Ipomoea batatas) often experiences yield reduction due to attacks by plant pests, particularly the stem borer Omphisa anastomosalis, which damages plant tissues and inhibits growth. The application of mulch can be an effort to improve the plant’s microenvironment while suppressing pest attacks. This study aimed to determine the level of damage caused by Omphisa anastomosalis under different mulch treatments. The research was conducted on farmers' rice fields located in Lingsar Village. The experiment used a Randomized Block Design (RBD) with three treatments: no mulch (control), black silver plastic mulch, and straw mulch, each repeated nine times, resulting in 27 experimental units. Data were analyzed using analysis of variance (ANOVA) at a 5% significance level, followed by the Honestly Significant Difference (HSD) test at the same level. The results showed that mulch type had a significant effect on stem diameter, pest population, and stem damage intensity in sweet potato plants. The plastic mulch treatment produced the highest stem diameter (20.45 mm), the highest pest population (7.33 individuals), and the highest stem damage intensity (59.53%), the straw mulch and control treatments showed lower values for all observed parameters.